2014
DOI: 10.3906/biy-1406-55
|View full text |Cite
|
Sign up to set email alerts
|

It takes 2 antioxidants to tango: the interaction between manganese superoxide dismutase and glutathione peroxidase-1

Abstract: The generation of ATP via oxidative phosphorylation provides the energy required by aerobic organisms to sustain themselves. This process is localized to the mitochondria, where electrons are passed among the components of the electron transport chain where there is an inevitability of leakage of the highly reactive oxygen species (ROS) superoxide, with it having been estimated that 1%-2% of the oxygen being used for mitochondrial respiration is converted to superoxide. With its short halflife and extreme reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, the insignificant decrease in GPX activity suggested that the quantity of hydrogen peroxide formed was high, and CAT was the most important factor in its removal. In addition, an important interaction between manganese SOD and GPX-1 was described in human cancer cells (Ekoue and Diamond, 2014). The elevated MDA level compared with the significant decrease in GST-specific activity indicated that this enzymatic activity was involved in MDA detoxification in an inefficient way.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the insignificant decrease in GPX activity suggested that the quantity of hydrogen peroxide formed was high, and CAT was the most important factor in its removal. In addition, an important interaction between manganese SOD and GPX-1 was described in human cancer cells (Ekoue and Diamond, 2014). The elevated MDA level compared with the significant decrease in GST-specific activity indicated that this enzymatic activity was involved in MDA detoxification in an inefficient way.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 35% inhibition in SOD activity in the liver tissue of S. aurata was attributed to the extension of lesions in the liver and drastic lipid infiltration in adipocytes due to Cd exposure (Souid et al, 2013). SOD activation may be due to excessive generation of ROS or inhibition as a result of direct damage to the SOD protein by increased H 2 O 2 content in the cell, whereas tissue-specific changes in SOD activity might be species-dependent (Ahmad et al, 2004;Puerto et al, 2010;Ekoue and Diamond, 2014). The activity of GPx can also be considered complementary to the activity of CAT, which is supported by the present data.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we analyzed the transcript levels of genes encoding cellular antioxidants in eukaryotic cells from yeast to mammalian (Ekoue and Diamond, 2014). The transcript levels of sod1 and ctt1, encoding superoxide dismutase and catalase, respectively, were analyzed in ird5 double mutants and 972 wild-type single mutants.…”
Section: Transcript Profiles Of Genes Related To the Oxidative Stressmentioning
confidence: 99%